Voice controlled mobile embedded device - Chong, Yi Xuan (2020)
This project is a voice-controlled robot project for academic purpose. It will provide readers with the introduction, literature review, system methodology and system design. The robot in this project will be called as Alexabot, and it is an Alexa based voicecontrolled robot. This robot is built-up by using GoPiGo, Raspberry Pi, speaker and USB microphone dongle. Amazon’s Alexa voice service will be implemented into the Raspberry Pi so that the robot will be able to use the AlexaPi service. This report will also review the current technologies, such as hardware platform, firmware/OS, database, programming language and algorithm. Besides, this project will also implement third party services which are ngrok and Flask into the robot. Other than that, this project will also contain a few functional modules which are voice recognition module, online searching module and robot movement module.